Emergent Nonreciprocal Circularly Polarized Emission from an Organic Thin Film. Issue 37 (30th July 2020) - Zinna, Francesco; Albano, Gianluigi; Taddeucci, Andrea; Colli, Tony; Aronica, Laura Antonella; Pescitelli, Gennaro; Di Bari, Lorenzo
Abstract: Controlling circularly polarized (CP) emission is key for both fundamental understanding and applications in the field of chiral photonics and electronics. Here, a completely new way to achieve this goal is presented. A luminescent thin film, made from a chiral conjugated phenylene bis‐thiophenylpropynone able to self‐assemble into ordered structures, emits highly circularly polarized light with opposite handedness from its two opposite faces. Such emergent nonreciprocal behavior in CP emission, so far unprecedented, represents a fundamental advance, opening new opportunities in design, preparation, and applications of CP emitting materials. Abstract : The thin film of a chiral π‐conjugated phenylene derivative emits circularly polarized (CP) light with a high degree of dissymmetry and opposite handedness from the two opposite faces of the film. Nonreciprocal CP emission is unreported so far, and it offers new opportunities in the design of CP emitting materials.